2014
DOI: 10.1016/j.wocn.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Treack or trit: Adaptation to genuine and arbitrary foreign accents by monolingual and bilingual listeners

Abstract: Two cross-modal priming experiments examined two questions about word recognition in foreign-accented speech: Does accent adaptation occur only for genuine accents markers, and does adaptation depend on language experience? We compared recognition of words spoken with canonical, genuinely-accented and arbitrarily-accented vowels. In Experiment 1, an Italian speaker pronounced vowels in English prime words canonically, or by lengthening /ɪ/ as in a genuine Italian accent (*/tri:k/ for trick), or by arbitrarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 49 publications
(63 reference statements)
3
31
0
2
Order By: Relevance
“…For example, in a primed auditory lexical decision task, Sumner and Samuel (2009) found that listeners having long-term experience with the New York City dialect recognized words with r-dropping (a typical feature of the dialect) more easily than listeners with little or no experience. Additionally, Weber et al (2014) found that native English listeners more readily adapt to markers of Italian-accented English that are consistent with previous experience than to arbitrary markers that do not align with a typical Italian accent. This suggests that listeners accumulate experiential knowledge, over which they may generalize and later avail themselves for more efficient processing of speech from new talkers of the same (or similar) accent.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…For example, in a primed auditory lexical decision task, Sumner and Samuel (2009) found that listeners having long-term experience with the New York City dialect recognized words with r-dropping (a typical feature of the dialect) more easily than listeners with little or no experience. Additionally, Weber et al (2014) found that native English listeners more readily adapt to markers of Italian-accented English that are consistent with previous experience than to arbitrary markers that do not align with a typical Italian accent. This suggests that listeners accumulate experiential knowledge, over which they may generalize and later avail themselves for more efficient processing of speech from new talkers of the same (or similar) accent.…”
Section: Introductionsupporting
confidence: 71%
“…From the work mentioned above (e.g., Dahan et al, 2008;Hanulíková & Weber, 2012;Reinisch & Weber, 2012;Witteman et al, 2013), as well as from other previous work (Sumner & Samuel, 2009;Weber, Di Betta, & McQueen, 2014;White, Yee, Blumstein, & Morgan, 2013), there is indication that listener experience (either short-term or long-term), may play a role in the ability to process accented speech. Apart from short-term adaptation, it appears that listeners also make use of long-term linguistic experience with accents to facilitate processing.…”
Section: Introductionmentioning
confidence: 85%
“…In addition, it has been shown that bilinguals have more flexibility in their phonetic‐to‐lexical mapping and can adapt to a novel accent better than monolinguals (Webber et al . ). Additionally, Baese‐Berk et al .…”
Section: The Gap In the Current Research And Suggestions For Future Rmentioning
confidence: 97%
“…The developmental course of their sound categorization also differs from monolingual children's (Creel 2012). In addition, it has been shown that bilinguals have more flexibility in their phonetic-tolexical mapping and can adapt to a novel accent better than monolinguals (Webber et al 2014). Additionally, Baese-Berk et al (2013) found that adults exposed to multiple non-native talkers were able to adapt to a novel accent, suggesting that exposure to this type of systematic variability improves word comprehension.…”
Section: The Gap In the Current Research And Suggestions For Future Rmentioning
confidence: 99%
“…There is ample evidence that listeners can adapt to a range of different types of variability in the speech signal, such as in synthetic (Fenn et al�, 2003;Greenspan, Nusbaum, and Pisoni, 1988), time-compressed (Dupoux and Green, 1997) or noise-vocoded speech (Rosen et al�, 1999), speech embedded in multi-speaker babble noise (Song et al�, 2012), and accents (Clarke and Garrett, 2004;Weber et al�, 2014)� In foreign-accented speech, for example, significant processing gains begin to emerge after exposure to only a few accented sentences (Clarke and Garrett, 2004;Weber et al�, 2014)� These studies have typically used either an increase in intelligibility, as measured by having listeners repeat or transcribe what they heard, or an increase in processing speed, as measured by reaction times in a comprehension-based task, as the dependent variable� A central question in the context of speaker-specific listening is whether this kind of learning, such as adapting to a foreign accent, can also generalise and aid in the comprehension of other speakers who speak with the same accent� This was investigated in a series of experiments on Chineseaccented English with American listeners by Bradlow and Bent (2008)� In their study, listeners were trained to become better at understanding Chinese-accented speech coming either from only one speaker or from several different speakers� After training, generalisation of learning was tested with speech materials from an unfamiliar speaker� For listeners in both conditions, intelligibility of the accented speech increased during train-ing� However, only after exposure to multiple speakers was there evidence of speaker-independent learning� Thus, the perceptual system seemed to treat the unfamiliar accent initially as a speaker idiosyncrasy, but was able to construct a more abstract representation of that accent after exposure to it from multiple speakers� This behaviour is adaptive in the sense that it would not be beneficial to apply learning about a speaker idiosyncrasy indiscriminately, since any given novel speaker is unlikely to have that same idiosyncrasy in their speech� It is beneficial however, to have a more abstract representation of non-standard features that apply to a larger group, because the learned representation can be applied immediately rather than having to go through the learning process over and over again for every encounter of a new speaker with that accent� While this type of empirical research has revealed important properties of perceptual learning about speakers, measuring global comprehension by testing at the lexical level, cannot identify what exactly it is in the speech signal that listeners are adapting to, or how they do it� However, a related series of studies has investigated how perceptual learning affects processing at a sublexical level, and the mechanisms that may be driving it� These experiments used an ambiguous speech stimulus, that is, a sound that falls on the category boundary between two phonemes, as a proxy for a speaker idiosyncrasy or a feature of an accent� Learning is measured by observing relatively subtle shifts in the categorisation of such ambiguous stimuli following a period of exposure� During exposure, listeners have different types of co...…”
Section: Adjusting Perceptual Categoriesmentioning
confidence: 99%